GRP-059 Ethanol Content in Chemotherapy. (12th March 2013) - Moreno, M; Gil, A; Diez, R; Molina, T
Abstract : Background: Ethanol is used as an excipient to enhance the solubility of substances partially soluble in water. For this reason, gemcitabine and paclitaxel, when supplied as an injection concentrate instead of lyophilized powder for reconstitution, contain large amounts of ethanol. The Spanish Pharmaceutical Association warns that quantities above 3 g/dose could affect the ability to drive and use machines and interfere with the effects of other drugs. Chemotherapy Compounding Units pharmacists consider already diluted vials easier to handle and are more willing to use them than vials with lyophilized powder. Purpose: To calculate the average ethanol dose given to oncology patients on gemcitabine and paclitaxel treatment. Materials and Methods: 6-month retrospective study (March–September 2012) of all patients who had received gemcitabine or paclitaxel. According to the summary of product characteristics, the ethanol content is: Gemcitabine (Actavis ® 2, 000 mg/50 ml): 9.875 mg ethanol/mg drug. Paclitaxel (Gp-pharm ® 300 mg/50 ml): 65.83 mg ethanol/ mg drug. Total ethanol dose was then calculated for each patient depending on the chemotherapy dose administered, as shown on clinical records. Results: View table . Conclusions: Ethanol given to these patients may be compared to moderate alcohol consumption. This, together with direct infusion into the blood and the short infusion time, makes it more likely that the ethanol will affect the patient and, thus, deserves attention. Special caution should be taken with those patients at higher risk (alcoholism, liver disease, epilepsy). Special care should also focus on others drugs the patient may take that might interact with ethanol. Patients should be advised not to drive or use machines soon after the chemotherapy treatment has been given and to inform the staff of any ethanol-related effect. When assessing new formulations, pharmacists should also consider the ethanol content apart from the convenience of dilution. No conflict of interest.